All-solid-state battery and preparation method thereof

By adding a first solid electrolyte with a low melting point to the positive electrode layer, solid electrolyte layer and negative electrode layer of the solid state battery, low temperature co-sintering is achieved, and the interface problem in the solid state battery preparation process is solved, which significantly reduces the solid-solid interface impedance and improves the performance and stability of the battery.

CN119833736APending Publication Date: 2025-04-15GUANGZHOU GREATER BAY TECH CO LTD
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
CN202510050081.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-13
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

The existing solid-state battery preparation process has interface problems, resulting in huge solid-solid interface impedance between each layer, affecting the performance and safety of the battery.

Method used

The first solid electrolyte with low melting point is added to the positive electrode layer, the solid electrolyte layer and the negative electrode layer, and the unbounded layer is achieved through low temperature co-sintering, thereby promoting the "unbounded" transmission of lithium ions.

Benefits of technology

It effectively eliminates the huge solid-solid interface impedance between the positive electrode layer, the solid electrolyte layer and the negative electrode layer, improves the overall density and cycling stability of the battery, and solves the problem of performance deterioration caused by internal pressure changes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119833736A_ABST
    Figure CN119833736A_ABST
Patent Text Reader

Abstract

The invention relates to an all-solid-state battery and a preparation method thereof, and belongs to the technical field of batteries, the all-solid-state battery comprises a positive electrode layer, a solid electrolyte layer and a negative electrode layer which are co-sintered; the positive electrode layer comprises a positive electrode active material and a first solid electrolyte; the solid electrolyte layer comprises a first solid electrolyte and a second solid electrolyte; the negative electrode layer comprises a negative electrode active material and a first solid electrolyte; the melting point of the first solid electrolyte is lower than that of the second solid electrolyte. The all-solid-state battery provided by the invention can effectively eliminate huge solid-solid interface impedance caused by assembly of the positive electrode, the solid electrolyte and the negative electrode in a traditional all-solid-state battery, and effectively solves the problem of performance deterioration caused by internal pressure change of the all-solid-state battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of battery technology, and in particular to an all-solid-state battery and a preparation method thereof. Background Art

[0002] With the continuous optimization and upgrading of electric vehicles, battery energy density has gradually become a bottleneck for the development of new energy. At the same time, battery safety issues have become increasingly prominent and have received widespread attention. Solid-state batteries replace electrolytes with solid electrolytes, solving the risks of battery combustion, explosion, and leakage. At the same time, they allow metallic lithium to be used in lithium batteries, which have the advantages of high safety and high energy density. The entire industry regards solid-state batteries as one of the important technical routes for the next generation of batteries.

[0003] Since there are no mature commercial solid-state batteries yet, and there is a lack of perfect solid-state battery preparation technology and special equipment, most solid-state batteries are produced in a similar way to traditional batteries. First, the positive electrode sheet, negative electrode sheet, solid electrolyte, etc. are prepared separately, and then stacked together in sequence. This preparation process has obvious interface problems, resulting in huge interface impedance between layers. In addition to the interface problems between the positive electrode, negative electrode and solid electrolyte, due to the lack of electrolyte infiltration, the gaps between the positive electrode particles cannot conduct lithium ions, and there are also interface problems between the positive electrode particles. Summary of the invention

[0004] In response to one or more technical problems existing in the prior art, the present invention provides an all-solid-state battery and a preparation method thereof. The all-solid-state battery provided by the present invention realizes low-temperature co-sintering of each layer by adding a first solid electrolyte with a low melting point in the positive electrode layer, the solid electrolyte layer and the negative electrode layer, thereby realizing the unboundedness between the positive electrode layer, the solid electrolyte layer and the negative electrode layer, and further realizing the "unbounded" transmission effect of lithium ions, which greatly eliminates the huge solid-solid interface impedance caused by the assembly between the positive electrode layer, the solid electrolyte layer and the negative electrode layer. At the same time, due to the integration of the positive electrode layer, the solid electrolyte layer and the negative electrode layer, the problem of performance deterioration caused by internal pressure changes of the all-solid-state battery can be effectively solved.

[0005] The present invention provides an all-solid-state battery, which comprises a co-sintered positive electrode layer, a solid electrolyte layer and a negative electrode layer; the positive electrode layer comprises a positive electrode active material and a first solid electrolyte; the solid electrolyte layer comprises a first solid electrolyte and a second solid electrolyte; the negative electrode layer comprises a negative electrode active material and a first solid electrolyte; in the positive electrode layer, the mass ratio of the positive electrode active material to the first solid electrolyte is 100:20-40; in the solid electrolyte layer, the mass ratio of the second solid electrolyte to the first solid electrolyte is 100:10-100; in the negative electrode layer, the mass ratio of the negative electrode active material to the first solid electrolyte is 100:20-40; the melting point of the first solid electrolyte is lower than the melting point of the second solid electrolyte.

[0006] Preferably, the first solid electrolyte is Li a MX b , wherein M is at least one of a Group III element, O, and S element, X is a halogen, a is 1 to 3, and b is 1 to 6; and / or

[0007] The second solid electrolyte is Li7La3Zr2O 12 , Li 10 GeP2S 12 , Li6PS5Cl, Li6PS5Br.

[0008] Preferably, the positive electrode active material is one of lithium iron phosphate, ternary nickel cobalt manganese, ternary nickel cobalt aluminum, lithium cobalt oxide, and lithium manganese oxide; and / or

[0009] The negative electrode active material is one of lithium titanate and graphite.

[0010] Preferably, the melting point of the first solid electrolyte is 80-350° C.; and / or

[0011] The melting point of the second solid electrolyte is greater than 500°C.

[0012] The present invention also provides a method for preparing the all-solid-state battery according to the first aspect, the preparation method comprising:

[0013] Casting and drying a positive electrode active slurry comprising a positive electrode active material, a first solid electrolyte, a positive electrode conductive agent, a binder, an auxiliary agent and a solvent to obtain a positive electrode active layer green body, and coating an aluminum paste on one side of the positive electrode active layer green body, and drying to obtain a positive electrode layer green body;

[0014] Casting and drying a solid electrolyte slurry comprising a first solid electrolyte, a second solid electrolyte, a binder, an additive and a solvent to obtain a solid electrolyte layer green body;

[0015] Casting and drying a negative electrode active slurry comprising a negative electrode active material, a first solid electrolyte, a negative electrode conductive agent, a binder, an auxiliary agent and a solvent to obtain a negative electrode active layer green body, and coating a copper slurry on one side of the negative electrode active layer green body, and drying to obtain a negative electrode layer green body;

[0016] The positive electrode layer green body, the solid electrolyte layer green body and the negative electrode layer green body are layered, and then subjected to hot pressing treatment, warm isostatic pressing treatment, degreasing treatment and sintering treatment to obtain an all-solid-state battery.

[0017] Preferably, the binder is at least one of polyvinyl butyral and polyvinylidene fluoride;

[0018] The auxiliary agent includes at least one of a plasticizer and a thickener; preferably, the plasticizer is dibutyl phthalate; the thickener is Span 80; and / or

[0019] The solvent is at least one of anhydrous ethanol and toluene.

[0020] Preferably, the temperature of the hot pressing treatment is 50-150° C., the pressure is 5-20 MPa, and the time is 1-10 min.

[0021] Preferably, the temperature of the warm isostatic pressing treatment is 50-80° C., the pressure is 50-70 MPa, and the time is 30-60 min.

[0022] Preferably, the degreasing treatment is carried out at a temperature of 150 to 250° C. and for a time of 10 to 20 hours.

[0023] Preferably, the sintering treatment is carried out at a temperature of 180 to 600° C. and for a time of 2 to 3 hours.

[0024] Compared with the prior art, the present invention has at least the following beneficial effects:

[0025] The all-solid-state battery provided by the present invention realizes low-temperature co-sintering of each layer by adding a low-melting-point first solid electrolyte as a low-temperature co-sintering aid in the positive electrode layer, the solid electrolyte layer and the negative electrode layer, which can effectively avoid the volatilization of lithium elements and ensure the uniform stability of the positive electrode layer, the solid electrolyte layer and the negative electrode layer materials. The first solid electrolyte with a low melting point is used to fully infiltrate the positive electrode layer and the negative electrode layer with the characteristics of a liquid electrolyte in a molten state, thereby improving the overall density of the battery, so that the active material particles inside the positive and negative electrodes, and the positive and negative electrodes and the solid electrolyte layer have good interface contact, realize the unboundedness between the positive electrode layer, the solid electrolyte layer and the negative electrode layer, realize the "unbounded" transmission effect of lithium ions, ensure the high-speed conduction of lithium ions inside the battery core, ensure that the all-solid-state battery has stable and excellent performance, greatly eliminate the huge solid-solid interface impedance caused by the assembly between the positive electrode layer, the solid electrolyte layer and the negative electrode layer, and at the same time, due to the integration of the positive electrode layer, the solid electrolyte layer and the negative electrode layer, the problem of performance deterioration caused by the internal pressure change of the all-solid-state battery can be effectively solved. The high melting point second solid electrolyte in the solid electrolyte layer acts as a skeleton and has very good temperature stability, so that the all-solid-state battery has good cycle stability. The present invention achieves low temperature co-sintering of each layer by regulating the content of the low melting point first solid electrolyte in each layer, thereby obtaining an all-solid-state battery with excellent comprehensive performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0027] Figure 1 is a schematic structural diagram of the all-solid-state battery provided by the present invention;

[0028] Figure 2 It is a cycle performance curve diagram of the all-solid-state battery provided by Example 1 of the present invention and Comparative Examples 1-3 and Comparative Examples 5-6.

[0029] Reference numerals:

[0030] 1-positive electrode layer; 11-positive electrode active layer; 12-aluminum film; 2-solid electrolyte layer; 3-negative electrode layer; 31-negative electrode active layer; 32-copper film. DETAILED DESCRIPTION

[0031] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0032] like Figure 1 The present invention provides an all-solid-state battery, which comprises a co-sintered positive electrode layer 1, a solid electrolyte layer 2 and a negative electrode layer 3; the positive electrode layer 1 comprises a positive electrode active material and a first solid electrolyte; the solid electrolyte layer 2 comprises a first solid electrolyte and a second solid electrolyte; the negative electrode layer 3 comprises a negative electrode active material and a first solid electrolyte; in the positive electrode layer 1, the mass ratio of the positive electrode active material to the first solid electrolyte is 100:20-40; in the solid electrolyte layer 2, the mass ratio of the second solid electrolyte to the first solid electrolyte is 100:10-100; in the negative electrode layer 3, the mass ratio of the negative electrode active material to the first solid electrolyte is 100:20-40; the melting point of the first solid electrolyte is lower than the melting point of the second solid electrolyte.

[0033] It should be noted that the thickness of the positive electrode layer and the negative electrode layer, and the amount of the positive electrode active material and the negative electrode material of the present invention can be the conventional thickness and amount in the field of all-solid-state batteries. The positive electrode layer includes an aluminum film (positive electrode current collector) 12 and a positive electrode active layer 11 located between the aluminum film (positive electrode current collector) 12 and the solid electrolyte layer 2. The negative electrode layer 3 includes a copper film (negative electrode current collector) 32 and a positive electrode active layer 31 located between the copper film (negative electrode current collector) 32 and the solid electrolyte layer 2. Figure 1 The area of ​​the middle current collector (aluminum film and copper film) is smaller than the area of ​​the active layer (positive electrode active layer and negative electrode active layer), which can effectively avoid short circuit.

[0034] The all-solid-state battery provided by the present invention realizes low-temperature co-sintering of each layer by adding a low-melting-point first solid electrolyte as a low-temperature co-sintering aid in the positive electrode layer, the solid electrolyte layer and the negative electrode layer, which can effectively avoid the volatilization of lithium elements and ensure the uniform stability of the positive electrode layer, the solid electrolyte layer and the negative electrode layer materials. The first solid electrolyte with a low melting point is used to fully infiltrate the positive electrode layer and the negative electrode layer with the characteristics of a liquid electrolyte in a molten state, thereby improving the overall density of the battery, so that the active material particles inside the positive and negative electrodes, and the positive and negative electrodes and the solid electrolyte layer have good interface contact, realize the unboundedness between the positive electrode layer, the solid electrolyte layer and the negative electrode layer, realize the "unbounded" transmission effect of lithium ions, ensure the high-speed conduction of lithium ions inside the battery core, ensure that the all-solid-state battery has stable and excellent performance, greatly eliminate the huge solid-solid interface impedance caused by the assembly between the positive electrode layer, the solid electrolyte layer and the negative electrode layer, and at the same time, due to the integration of the positive electrode layer, the solid electrolyte layer and the negative electrode layer, the problem of performance deterioration caused by the internal pressure change of the all-solid-state battery can be effectively solved. The high melting point second solid electrolyte in the solid electrolyte layer acts as a skeleton and has very good temperature stability, so that the all-solid-state battery has good cycle stability. The present invention achieves low temperature co-sintering of each layer by regulating the content of the low melting point first solid electrolyte in each layer, thereby obtaining an all-solid-state battery with excellent cycle performance.

[0035] According to some preferred embodiments, the first solid electrolyte is Li a MX b , wherein M is at least one of the third main group elements, O, and S elements, X is a halogen, a is 1-3, and b is 1-6.

[0036] According to some preferred embodiments, the second solid electrolyte is Li7La3Zr2O 12 (LLZO), Li 10 GeP2S 12 One of (LGPS), Li6PS5Cl, and Li6PS5Br.

[0037] According to some preferred embodiments, the positive electrode active material is one of lithium iron phosphate (LFP), ternary nickel cobalt manganese (NCM), ternary nickel cobalt aluminum (NCA), lithium cobalt oxide (LCO), and lithium manganese oxide.

[0038] According to some preferred embodiments, the negative electrode active material is one of lithium titanate and graphite.

[0039] According to some preferred embodiments, the melting point of the first solid electrolyte is 80-350°C.

[0040] According to some preferred embodiments, the melting point of the second solid electrolyte is greater than 500°C.

[0041] The present invention also provides a method for preparing the all-solid-state battery according to the first aspect, the preparation method comprising:

[0042] Casting and drying a positive electrode active slurry comprising a positive electrode active material, a first solid electrolyte, a positive electrode conductive agent, a binder, an auxiliary agent and a solvent to obtain a positive electrode active layer green body, and coating an aluminum paste on one side of the positive electrode active layer green body, and drying to obtain a positive electrode layer green body;

[0043] Casting and drying a solid electrolyte slurry comprising a first solid electrolyte, a second solid electrolyte, a binder, an additive and a solvent to obtain a solid electrolyte layer green body;

[0044] Casting and drying a negative electrode active slurry comprising a negative electrode active material, a first solid electrolyte, a negative electrode conductive agent, a binder, an auxiliary agent and a solvent to obtain a negative electrode active layer green body, and coating a copper slurry on one side of the negative electrode active layer green body, and drying to obtain a negative electrode layer green body;

[0045] The positive electrode layer green body, the solid electrolyte layer green body and the negative electrode layer green body are layered, and then subjected to hot pressing treatment, warm isostatic pressing treatment, degreasing treatment and sintering treatment to obtain an all-solid-state battery.

[0046] The preparation method of the all-solid-state battery of the present invention first prepares a positive electrode active layer green body and a negative electrode active layer green body containing a first solid electrolyte by tape casting, and then coats the positive electrode active layer green body and the negative electrode active layer green body with aluminum paste and copper paste respectively, and obtains a positive electrode layer green body and a negative electrode layer green body after drying, and then stacks the positive electrode layer green body, the solid electrolyte layer and the negative electrode layer green body, and adheres the layers together by hot pressing, and further achieves tight stacking between the layers by warm isostatic pressing, and removes the solvent and most of the adhesive in the green body after stacking by degreasing. Finally, the low melting point characteristic of the first solid electrolyte is used to realize low-temperature co-sintering of each layer, and the remaining binder and additives are removed by sintering. At the same time, an aluminum film and a copper film (acting as the positive electrode collector and the negative electrode collector, respectively) formed by the tight accumulation of aluminum powder particles and copper powder particles are obtained on the surface of the positive electrode active layer and the negative electrode active layer, respectively, truly realizing the unboundedness between the positive electrode layer, the solid electrolyte layer and the negative electrode layer. The cycle performance of the all-solid-state battery is improved by controlling the content of the first solid electrolyte in each layer, and finally an all-solid-state battery with excellent comprehensive performance is obtained.

[0047] It should be noted that the present invention adopts the method of coating aluminum paste and copper paste on the positive active layer green body and the negative active layer green body respectively, and forming aluminum film and copper film serving as positive current collector and negative current collector respectively on the surface of the positive active layer and the negative active layer by co-sintering. This can effectively overcome the problem that the current collector (positive current collector or negative current collector) and the active layer (positive active material or negative active material) are easily separated during the sintering process when the active slurry (positive active slurry or negative active slurry) is coated on the surface of the current collector (positive current collector or negative current collector).

[0048] The present invention does not specifically limit the sources and types of copper paste and aluminum paste. Commercially available copper paste (FPE-Cu-002, FPE-Cu-003, etc. from Ningbo Flexographic Electronic Technology Co., Ltd.) and aluminum paste (the aluminum paste is ZL-AL6055 aluminum paste from Shenzhen Zhenglan Industrial Co., Ltd.) can be used.

[0049] The present invention can prepare an ultra-thin solid electrolyte membrane (solid electrolyte layer) through a tape casting process, and its actual thickness after sintering can be adjusted in the range of 1 to 50 μm, providing huge space for improving the energy density of all-solid-state batteries.

[0050] According to some preferred embodiments, the positive electrode conductive agent is one or more of carbon black, acetylene black, carbon fiber, and carbon nanotubes, preferably Ketjen black; in the positive electrode layer, the mass ratio of the positive electrode active material to the positive electrode conductive agent is 100:4-6;

[0051] According to some preferred embodiments, the negative electrode conductive agent is one or more of graphite, acetylene black, carbon fiber, and carbon nanotubes; in the negative electrode layer, the mass ratio of the negative electrode active material to the negative electrode conductive agent is 100:2-4;

[0052] According to some preferred embodiments, the binder is at least one of polyvinyl butyral and polyvinylidene fluoride; in the positive electrode layer, the mass ratio of the positive electrode active material to the binder is 100:8-12; in the solid electrolyte layer, the mass ratio of the second solid electrolyte to the binder is 100:8-12; in the negative electrode layer, the mass ratio of the negative electrode active material to the binder is 100:8-12.

[0053] According to some preferred embodiments, the auxiliary agent includes at least one of a plasticizer and a thickener; preferably, the plasticizer is dibutyl phthalate; and the thickener is Span 80. In the positive electrode layer, the mass ratio of the positive electrode active material to the auxiliary agent is 100:3-7; in the solid electrolyte layer, the mass ratio of the second solid electrolyte to the auxiliary agent is 100:3-7; in the negative electrode layer, the mass ratio of the negative electrode active material to the auxiliary agent is 100:3-7.

[0054] According to some preferred embodiments, the solvent is at least one of anhydrous ethanol and toluene.

[0055] According to some preferred embodiments, the temperature of the hot pressing treatment is 50-150°C (for example, it can be 50°C, 60°C, 80°C, 100°C, 120°C or 150°C), the pressure is 5-20MPa (for example, it can be 5MPa, 6MPa, 8MPa, 10MPa, 12MPa, 15MPa, 16MPa, 18MPa or 20MPa), and the time is 1-10min (for example, it can be 1min, 2min, 5min, 6min, 8min or 10min).

[0056] According to some preferred embodiments, the temperature of the warm isostatic pressing treatment is 50-80°C (for example, it can be 50°C, 55°C, 60°C, 65°C, 70°C, 75°C or 80°C), the pressure is 50-70MPa (for example, it can be 50MPa, 55MPa, 60MPa, 65MPa or 70MPa), and the time is 30-60min (for example, it can be 30min, 35min, 40min, 45min, 50min, 55min or 60min).

[0057] According to some preferred embodiments, the degreasing treatment is carried out at a temperature of 150 to 250°C (for example, 150°C, 160°C, 180°C, 200°C, 220°C or 250°C) and for a time of 10 to 20h (for example, 10h, 12h, 15h, 16h, 18h or 20h).

[0058] According to some preferred embodiments, the sintering treatment is carried out at a temperature of 180 to 600°C (for example, 180°C, 200°C, 250°C, 300°C, 350°C, 400°C, 450°C, 500°C, 550°C or 600°C), and the time is 2 to 3h (for example, 2h, 2.5h or 3h).

[0059] In order to more clearly illustrate the technical solutions and advantages of the present invention, the present invention is further described below in conjunction with embodiments.

[0060] Example 1

[0061] An all-solid-state battery includes a co-sintered positive electrode layer, a solid electrolyte layer and a negative electrode layer, and a preparation method of the all-solid-state battery includes:

[0062] Preparation of positive electrode layer green body: casting and drying the positive electrode active slurry (drying temperature is 80° C., time is 10 h) to obtain a positive electrode active layer green body; aluminum slurry is brushed on one side of the positive electrode active layer green body, and dried to obtain a positive electrode layer green body;

[0063] Preparation of solid electrolyte layer green body: casting and drying the solid electrolyte slurry (drying temperature is 80° C., time is 10 h) to obtain a solid electrolyte layer green body;

[0064] Preparation of negative electrode layer green body: negative electrode active slurry is tape-cast and dried (drying temperature is 80°C, time is 10h) to obtain negative electrode active layer green body; copper slurry is brushed on one side of the negative electrode active layer green body, and dried (drying temperature is 80°C, time is 2h) to obtain negative electrode layer green body; wherein, the formula of positive electrode active slurry, solid electrolyte slurry and negative electrode active slurry is shown in Table 1.

[0065] Table 1. Formulas of positive electrode active slurry, solid electrolyte slurry and negative electrode active slurry in Example 1

[0066]

[0067] The inner side of the positive electrode layer green body (away from the side where the aluminum paste is applied), the solid electrolyte layer green body and the inner side of the negative electrode layer green body (away from the side where the copper paste is applied) are stacked in sequence, and then the stacked green bodies are subjected to hot pressing treatment (temperature of 80°C, pressure of 10MPa, time of 5min), warm isostatic pressing treatment (temperature of 60°C, pressure of 60MPa, time of 60min), degreasing heat treatment (temperature of 150°C, time of 12h) and low-temperature sintering heat treatment (temperature of 300°C, treatment time of 2h) to obtain an all-solid-state battery.

[0068] Example 2

[0069] It is basically the same as Example 1, with the only difference being that the positive electrode active material is ternary nickel-cobalt-manganese (NCM811), wherein the temperature for hot pressing is 50°C, the pressure is 20MPa, and the time is 10min; the temperature for warm isostatic pressing is 50°C, the pressure is 70MPa, and the time is 60min; the temperature for degreasing heat treatment is 150°C, and the time is 12h; the temperature for low-temperature sintering heat treatment is 290°C, and the treatment time is 2h.

[0070] Example 3

[0071] It is basically the same as Example 1, with the only difference being that the positive electrode active material is lithium cobalt oxide (LCO), wherein the temperature of the hot pressing treatment is 150°C, the pressure is 5 MPa, and the time is 1 min; the temperature of the warm isostatic pressing treatment is 80°C, the pressure is 50 MPa, and the time is 30 min; the temperature of the degreasing heat treatment is 150°C, and the time is 12 h; the temperature of the low-temperature sintering heat treatment is 294°C, and the treatment time is 2 h.

[0072] Example 4

[0073] It is basically the same as Example 1, except that the second solid electrolyte is Li7La3Zr2O 12 (LLZO), wherein the temperature of hot pressing treatment is 80°C, the pressure is 10MPa, and the time is 5min; the temperature of warm isostatic pressing treatment is 60°C, the pressure is 60MPa, and the time is 60min; the temperature of degreasing heat treatment is 250°C, and the time is 10h; the temperature of low-temperature sintering heat treatment is 550°C, and the treatment time is 3h.

[0074] Example 5

[0075] The same as Example 1, except that the second solid electrolyte is Li 10 GeP2S 12 (LGPS), the sintering temperature is 450℃.

[0076] Example 6

[0077] It is basically the same as Example 1, except that the first solid electrolyte is LiGaCl4 (melting point is 175°C) and the sintering temperature is 310°C.

[0078] Example 7

[0079] It is basically the same as Example 1, except that the first solid electrolyte is Li3OI (melting point is 80°C) and the sintering temperature is 180°C.

[0080] Example 8

[0081] It is basically the same as Example 1, except that the first solid electrolyte is Li3OF (melting point is 350°C) and the sintering temperature is 600°C.

[0082] Example 9

[0083] It is basically the same as Example 1, except that: the amount of the first solid electrolyte in the positive electrode active slurry is 40 parts, the amount of the first solid electrolyte material in the solid electrolyte slurry is 100 parts, and the amount of the first solid electrolyte in the negative electrode active slurry is 40 parts; the sintering temperature is 250°C.

[0084] Example 10

[0085] It is basically the same as Example 1, except that the amount of the first solid electrolyte in the positive electrode active slurry is 20 parts, the amount of the first solid electrolyte material in the solid electrolyte slurry is 50 parts, the amount of the first solid electrolyte in the negative electrode active slurry is 20 parts, and the sintering temperature is 350°C.

[0086] Embodiment 11

[0087] It is basically the same as Example 1, except that the amount of the first solid electrolyte in the positive electrode active slurry is 20 parts, the amount of the first solid electrolyte material in the solid electrolyte slurry is 10 parts, the amount of the first solid electrolyte in the negative electrode active slurry is 20 parts, and the sintering temperature is 200°C.

[0088] Comparative Example 1

[0089] The method is basically the same as Example 1, except that the positive electrode active slurry does not contain the first solid electrolyte.

[0090] Comparative Example 2

[0091] The method is basically the same as Example 1, except that the solid electrolyte slurry does not contain the first solid electrolyte.

[0092] Comparative Example 3

[0093] The method is basically the same as Example 1, except that the negative electrode active slurry does not contain the first solid electrolyte.

[0094] Comparative Example 4

[0095] The method is basically the same as Example 1, except that the positive electrode active slurry, the solid electrolyte slurry and the negative electrode active slurry do not contain the first solid electrolyte.

[0096] Experiments have found that the co-sintering temperature cannot be found under this condition, and the sintered battery cells at any temperature will have various defects such as obvious interface impedance and interface cracking.

[0097] Comparative Example 5

[0098] It is basically the same as Example 1, except that the solid electrolyte in the solid electrolyte slurry is all the first solid electrolyte, and the sintering temperature is 290°C.

[0099] Experiments have found that when the solid electrolytes in the solid electrolyte slurry are all low-melting-point first solid electrolytes, co-sintering can be achieved at 290°C. However, the all-solid-state diaphragm composed only of the low-melting-point first solid electrolyte is prone to phase transition and performance deterioration during long-term operation, resulting in poor stability of the sintered all-solid-state battery, and then poor long-cycle life performance.

[0100] Comparative Example 6

[0101] It is basically the same as Example 1, except that the amount of the first solid electrolyte in the positive electrode active slurry is 60 parts, the amount of the first solid electrolyte in the negative electrode active slurry is 60 parts, and the sintering temperature is 280°C.

[0102] Experiments have found that this comparative example can achieve co-sintering at 280°C, but because the amount of the low-melting-point first solid electrolyte used is too large, the low-melting-point first solid electrolyte is prone to phase transformation during the operation of the all-solid-state battery, resulting in poor stability of the sintered all-solid-state battery and poor cycle performance.

[0103] The performance of the all-solid-state batteries provided in the embodiments of the present invention and the comparative examples were tested, and the specific testing methods are as follows:

[0104] The all-solid-state battery was connected to the NEWARE battery test system, aged for 3 cycles at a charge and discharge rate of 0.05C, and then subjected to a charge and discharge cycle test at 0.1C, and the battery's first-week discharge capacity and the discharge capacity after 100 cycles were recorded. The capacity retention rate (%) after 100 cycles was calculated as follows: discharge capacity after 100 cycles / discharge capacity after the first cycle × 100%.

[0105] Table 1. Performance data of all-solid-state batteries prepared in various embodiments of the present invention and comparative examples

[0106]

[0107] As can be seen from Table 1, the embodiment of the present invention can achieve low-temperature co-sintering by introducing a low-melting-point first solid electrolyte into the positive electrode layer, the solid electrolyte layer and the negative electrode layer, thereby obtaining an all-solid-state battery with excellent comprehensive performance. It should be noted that the discharge capacity of Example 2 is significantly higher than that of other embodiments because the positive electrode active material ternary nickel-cobalt-manganese (NCM811) itself has a higher theoretical capacity.

[0108] Compared with Example 1, in Comparative Example 1, a low-melting-point solid electrolyte was not introduced into the positive electrode layer, resulting in the inability of the positive electrode layer and the solid electrolyte layer to form a tight co-sintering, and the inability to form a good contact inside the positive electrode layer, resulting in the formation of an obvious ion transfer impedance between the positive electrode and the solid electrolyte, which reduces the capacity of the all-solid-state battery and deteriorates the cycle performance.

[0109] Compared with Example 1, in Comparative Example 2, a low-melting-point solid electrolyte was not introduced into the solid electrolyte layer, resulting in the inability of the positive electrode layer and the negative electrode layer to form a tight co-sintering with the solid electrolyte layer, resulting in obvious ion transfer impedance between the positive electrode, the negative electrode and the solid electrolyte, which reduces the capacity of the all-solid-state battery and deteriorates the cycle performance.

[0110] Compared with Example 1, in Comparative Example 3, a low-melting-point solid electrolyte was not introduced into the negative electrode layer, resulting in the inability of the negative electrode layer and the solid electrolyte layer to form a tight co-sintering, and the inability to form a good contact inside the negative electrode layer, resulting in a significant ion transfer impedance between the negative electrode and the solid electrolyte, which reduces the capacity of the all-solid-state battery and deteriorates the cycle performance.

[0111] Compared with Example 1, no low-melting-point solid electrolyte is introduced into the positive electrode layer, solid electrolyte layer and negative electrode layer in Comparative Example 4. Under this condition, the co-sintering temperature cannot be found. The sintered battery cell at any temperature will have various defects such as obvious interface impedance and interface cracking, and performance testing cannot be carried out.

[0112] Compared with Example 1, the solid electrolyte in the solid electrolyte layer in Comparative Example 5 is entirely the first solid electrolyte and does not contain the second solid electrolyte. Since the solid electrolyte layer composed only of the first solid electrolyte with a low melting point is prone to phase transition and performance deterioration during long-term operation, the stability of the sintered all-solid-state battery is poor, which in turn leads to poor long cycle life performance.

[0113] Compared with Example 1, the content of the first solid electrolyte in the positive electrode layer and the negative electrode layer in Comparative Example 6 is too high. During the operation of the all-solid-state battery, the low-melting-point first solid electrolyte is prone to phase transformation, resulting in poor stability and poor cycle performance of the sintered all-solid-state battery.

[0114] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. An all-solid-state battery, characterized in that: The all-solid-state battery includes a co-sintered positive electrode layer, a solid electrolyte layer and a negative electrode layer; the positive electrode layer includes a positive electrode active material and a first solid electrolyte; the solid electrolyte layer includes a first solid electrolyte and a second solid electrolyte; the negative electrode layer includes a negative electrode active material and a first solid electrolyte; in the positive electrode layer, the mass ratio of the positive electrode active material to the first solid electrolyte is 100:20-40; in the solid electrolyte layer, the mass ratio of the second solid electrolyte to the first solid electrolyte is 100:10-100; in the negative electrode layer, the mass ratio of the negative electrode active material to the first solid electrolyte is 100:20-40; the melting point of the first solid electrolyte is lower than the melting point of the second solid electrolyte.

2. The all-solid-state battery according to claim 1, characterized in that: The first solid electrolyte is Li a MX b , wherein M is at least one of a Group III element, O, and S element, X is a halogen, a is 1 to 3, and b is 1 to 6; and / or The second solid electrolyte is Li7La3Zr2O 12 , Li 10 GeP2S 12 , Li6PS5Cl, Li6PS5Br.

3. The all-solid-state battery according to claim 1, characterized in that: The positive electrode active material is one of lithium iron phosphate, ternary nickel cobalt manganese, ternary nickel cobalt aluminum, lithium cobalt oxide, and lithium manganese oxide; and / or The negative electrode active material is one of lithium titanate and graphite.

4. The all-solid-state battery according to claim 1, characterized in that: The melting point of the first solid electrolyte is 80 to 350° C.; and / or The melting point of the second solid electrolyte is greater than 500°C.

5. A method for preparing an all-solid-state battery according to any one of claims 1 to 4, characterized in that: The preparation method comprises: Casting and drying a positive electrode active slurry comprising a positive electrode active material, a first solid electrolyte, a positive electrode conductive agent, a binder, an auxiliary agent and a solvent to obtain a positive electrode active layer green body, and coating an aluminum paste on one side of the positive electrode active layer green body, and drying to obtain a positive electrode layer green body; Casting and drying a solid electrolyte slurry comprising a first solid electrolyte, a second solid electrolyte, a binder, an additive and a solvent to obtain a solid electrolyte layer green body; Casting and drying a negative electrode active slurry comprising a negative electrode active material, a first solid electrolyte, a negative electrode conductive agent, a binder, an auxiliary agent and a solvent to obtain a negative electrode active layer green body, and coating a copper slurry on one side of the negative electrode active layer green body, and drying to obtain a negative electrode layer green body; The positive electrode layer green body, the solid electrolyte layer green body and the negative electrode layer green body are layered, and then subjected to hot pressing treatment, warm isostatic pressing treatment, degreasing treatment and sintering treatment to obtain an all-solid-state battery.

6. The preparation method according to claim 5, characterized in that: The binder is at least one of polyvinyl butyral and polyvinylidene fluoride; The auxiliary agent includes at least one of a plasticizer and a thickener; preferably, the plasticizer is dibutyl phthalate; the thickener is Span 80; and / or The solvent is at least one of anhydrous ethanol and toluene.

7. The preparation method according to claim 5, characterized in that: The temperature of the hot pressing treatment is 50-150° C., the pressure is 5-20 MPa, and the time is 1-10 min.

8. The preparation method according to claim 5, characterized in that: The temperature of the warm isostatic pressing treatment is 50-80° C., the pressure is 50-70 MPa, and the time is 30-60 min.

9. The preparation method according to claim 5, characterized in that: The degreasing treatment is performed at a temperature of 150 to 250° C. and for a time of 10 to 20 hours.

10. The preparation method according to claim 5, characterized in that: The sintering treatment is carried out at a temperature of 180 to 600° C. and for a time of 2 to 3 hours.

Citation Information

Patent Citations

  • Preparation method of novel all-solid-state lithium ion battery

    CN110233298A

  • Laminated co-sintered piezoelectric ceramic device and compensation glue slurry used by same

    CN110534637A

  • Preparation method of arched flaky dielectric material and flexural voltage electric composite material

    CN110759718A

  • All-solid-state battery and preparation method thereof

    CN116247158A

  • Lithium lanthanum zirconium oxide all-solid-state battery and preparation method thereof

    CN117558992A